Development of an Integrated Computer Code System for Analyzing Irradiation Behaviors of a Fast Reactor Fuel. (3rd August 2021) - Uwaba, Tomoyuki; Nemoto, Junichi; Ito, Masahiro; Ishitani, Ikuo; Doda, Norihiro; Tanaka, Masaaki; Ohtsuka, Satoshi
Abstract: Computer codes for irradiation behavior analysis of a fuel pin and a fuel pin bundle and for coolant thermal-hydraulic analysis were coupled into an integrated code system. In the system, each code provides data required by other codes, and the analyzed results are shared among them. The system allows for the synthesizing of analyses of thermal, chemical, and mechanical behaviors in a fuel subassembly under irradiation. A test analysis was made for a fuel subassembly containing a mixed oxide fuel pin bundle irradiated in a fast reactor. The results of the analysis were presented with transverse cross-sectional images of the fuel subassembly and three-dimensional images of a fuel pin and fuel pin bundle models. For detailed evaluation, various irradiation behaviors of all fuel pins in the subassembly were analyzed and correlated with irradiation conditions.